Nesting Technique as A Simple Method for Optimal Outcomes in Premature Infant Care: A Literature Review - Indartik Indartik; Nopi Nur Khasanah; Sri Wahyuni (GLOBAL HEALTH SCIENCE GROUP, 2025)
Preterm birth accounts for up to two-thirds of total cases worldwide. Premature infants often face challenges in adapting to life outside the womb due to immature organ development. Nesting is a method designed to create an environment resembling conditions in the womb by positioning the infant's body in a flexed posture and surrounding it with rolled cloth. This study aims to identify the physiological and psychological benefits of nesting while also providing evidence-based implementation guidelines for neonatal clinical practice. This study utilized a literature review design guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Article searches were conducted through electronic databases, including PubMed, Google Scholar, Crossref, OpenAlex, and Semantic Scholar. The search keywords used the Boolean operator (AND):